Keefektifan Teknik Konseling Self-Modeling Untuk Meningkatkan Rasa Percaya Diri Siswa di SMP Negeri 19 Pontianak - Dea Aristia; Muhamad Asrori; Halida (Jurnal Dunia Pendidikan, 2023)
in this study, class VII students at SMP Negeri 19 Pontianak will have their self-confidence tested to see how well group counseling using the self-modeling technique performs. Based on these issues, the researcher aims to see if using self-modeling strategies in group therapy will help students feel more confident. Pre-Experimental Design with a Pre-Test - Post-Test One Group Design was the study methodology that was employed. Purposive sampling was used to select subjects or samples using a non-probability sampling technique. Seven individuals with poor self-esteem were selected at random from a group of 70 people; these individuals were class VII students. According to the computations, the average pre-test value was 71 and the average post-test value was 114 before treatment. The Paired Sample T-test is then used to generate a T count of -24.631 and a Sig (2 tailed) value of 0.00 0.05, indicating that Ho is rejected and Ha is accepted. As a result, there was a noticeable difference between the students' levels of self-confidence before and after receiving group counseling at SMP Negeri 19 Pontianak to boost class VII students' self-confidence using a self-modeling strategy.